PEMIKIRAN KIAI SAHAL MAHFUDH TENTANG PERAN PUBLIK PEREMPUAN DI ERA MILENIAL - Asofik, Mohammad Rif’an (JURNAL AL-IJTIMAIYYAH, 2023)
Abstract: This research investigates Kiai Sahal Mahfudh opinion about the public roles of women in the recent era. This discourse becomes interesting for some authors since there are still some Muslim people who discriminates the role of women and place women as domestic resident. These contemporary issues about the role of women in public scope become a fascinating issue to be discussed among the educational activist. For instance, how is the law of a woman who becomes a leader? Whether or not if a woman is allowed to have a carrier in the political and entrepreneur field, or even becomes a foreign labour? This matter still produces different point of views and opinions among the people. To some extend it is considered as completely haram by showing some of their arguments, while to some others it is considered as halal because of some fundamental reasons. These two different opinions are the reasons why the researcher feels like to initiate the research by collaborating Kiai Sahal Mahfudh opinion in answering such matter as well as knowing the methodology of his thought. This research uses qualitative research with library research approach. The result of the research proves that the three methods of Kiai Sahal Mahfudh’s opinion make women’s rights are preserved as what is in the Islamic teachings, so that women can play their public role in the millennial era.Keywords:  Kiai Sahal Mahfudh Thought; Women’s Public Roles; Millennial Era.Abstrak: Tulisan ini mengkaji pemikiran Kiai Sahal Mahfudh tentang peran publik perempuan di era milenial, yang mana diskursus ini menjadi begitu menarik bagi penulis sebab masih ada sebagian orang Islam yang masih mendiskriminasikan peran perempuan dan memposisikan perempuan sebagai manusia domestik. Isu-isu kontemporer tentang peran perempuan di dunia publik menjadi tema yang menarik untuk dikonsumsi civitas akademik. Misalnya, bagaimana hukum perempuan menjadi pemimpin? Apakah boleh dalam Islam, perempuan (istri) berkarir di dunia politik, entrepreneurship, bahkan menjadi TKW?. Problematika tersebut masih menimbulkan silang pendapat, ada yang mengatakan tidak boleh (haram) secara mutlak dengan memaparkan argumentasinya. Di sisi lain juga ada yang menyampaikan boleh (halal) disebabkan beberapa alasan yang fundamental. Dari dua silang pendapat itulah penulis merasa terpanggil untuk mengelaborasi pemikiran Kiai Sahal Mahfudh dalam menjawab problematika tersebut sekaligus mengetahui metodologi berpikirnya. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan library research. Hasil dari penelitian ini adalah bahwa ketiga metodologi pemikiran Kiai Sahal Mahfudh inilah yang menjadikan hak-hak perempuan dapat terjaga sebagaimana yang ada dalam syariat Islam sehingga perempuan dapat memainkan peran publiknya di era milenial.Kata Kunci: Pemikiran Kiai Sahal Mahfudh; Peran Publik Perempuan; Era Milenial.